Ovine FABP4 Variation and Its Association With Flystrike Susceptibility - Burrows, L. E. R.; Zhou, H.; Frampton, C. M. A.; Forrest, R. H. J.; Hickford, J. G. H. (Frontiers in Genetics, 2021)
Flystrike is a major cost and a welfare issue for the New Zealand sheep industry. There are several factors that can predispose sheep to flystrike, such as having fleecerot, a urine-stained breech, and ‘dags’ (an accumulation of faecal matter in the wool of the breech). The FABP4 gene (FABP4) has been associated with variation in ovine fleecerot resistance, with a strong genetic correlation existing between fleecerot and flystrike occurrence. In this study, blood samples were collected from sheep with and without flystrike for DNA typing. PCR-SSCP analyses were used to genotype two regions of ovine FABP4. Sheep with the A1 variant of FABP4 were found to be less likely (odds ratio 0.689, P = 0.014) to have flystrike than those without A1. The likelihood of flystrike occurrence decreased as copy number of A1 increased (odds ratio 0.695, P = 0.006). This suggests that FABP4 might be a candidate gene for flystrike resilience in sheep, although further research is required to verify this association.